2017
DOI: 10.1159/000481263
|View full text |Cite
|
Sign up to set email alerts
|

Ulcerative Colitis: Are We Neglecting Its Progressive Character

Abstract: "lead pipe," 16% with pseudopolyps, and 3% with stenosis and fibrous bridges. Reference to functional anorectal disorders was identified in 49%, mostly previous and self-limited episodes of incontinence, but including persistent incontinence in 10% (CCIS 8 ± 4.8). There was an increased incidence of structural damage and anorectal dysfunction in patients who needed corticosteroid therapy (p = 0.001), immunosuppressants (p < 0.001), and anti-TNFs (p = 0.002) and an association of structural damage with anorecta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Therefore, we performed subgroup analysis considering different step‐up approaches individually confirming the same predictive risk for IMM and biological therapies. Evaluating risks for colonic extension, endoscopic progressive features and EIMs, our findings are in agreement with previous studies, providing new evidence about extent progression associated to biological therapy and EIM appearance related with IMM use 20–24 . An important point is the association of age and immunosuppressive therapy use, differing from the Swiss IBD cohort registry and the ACCESS Group observations 20 , 25 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Therefore, we performed subgroup analysis considering different step‐up approaches individually confirming the same predictive risk for IMM and biological therapies. Evaluating risks for colonic extension, endoscopic progressive features and EIMs, our findings are in agreement with previous studies, providing new evidence about extent progression associated to biological therapy and EIM appearance related with IMM use 20–24 . An important point is the association of age and immunosuppressive therapy use, differing from the Swiss IBD cohort registry and the ACCESS Group observations 20 , 25 .…”
Section: Discussionsupporting
confidence: 89%
“…Evaluating risks for colonic extension, endoscopic progressive features and EIMs, our findings are in agreement with previous studies, providing new evidence about extent progression associated to biological therapy and EIM appearance related with IMM use. [20][21][22][23][24] An important point is the association of age and immunosuppressive therapy use, differing from the Swiss IBD cohort registry and the ACCESS Group observations. 20,25 In terms of surgery, extensive colitis, previous exposure to IMM, steroid refractoriness and disease diagnosis in the prebiologic era were shown to impact the likelihood of the patient requiring a colectomy; these results are in keeping with previously published articles.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Although the advent of biologics like the anti-tumour necrosis factor (TNF)-antibodies infliximab, adalimumab and golimumab, and more recently the anti-integrin-antibody vedolizumab, have substantially improved the therapeutic options in UC, 3 mucosal healing rates are low and still 10–16% of patients lose their colon due to therapy-refractory situations. 1,4 In addition, reluctance to use potent drugs earlier in the course of their disease 5 and the structural damage due to ongoing inflammation 6,7 could contribute to this dilemma.…”
Section: Introductionmentioning
confidence: 99%
“…In the population presented by Massinha et al [9], proximal disease extension was found in 12% of the patients, strictures in 3%, pseudopolyposis in 16%, and bridging fibrosis in 3%, and 15% of the patients presented a "lead pipe" colon on colonoscopy. Interestingly, anorectal dysfunction was reported in 49% of the patients, as evaluated by the CCIS score, 10% of which had persistent symptoms of incontinence.…”
mentioning
confidence: 87%
“…In this issue of GE -Portuguese Journal of Gastroenterology, Massinha et al [9] presented a retrospective study including 104 patients with UC, currently living in a tertiary referral hospital area, in whom they evaluated the presence of structural and functional bowel damage.…”
mentioning
confidence: 99%